Lord Dufferin, Ireland and the British Empire, c. 1820-1900 rule by the best? - Tindley, Annie ca. 20./21. Jh (Routledge Taylor & Francis Group, 2021)
"This book explores the life and career of Frederick Hamilton Temple Blackwood, 1st marquess of Dufferin and Ava (1826-1902). Dufferin was a landowner in Ulster, an urbane diplomat, literary sensation, courtier, politician, colonial governor, collector, son, husband and father. It draws on episodes from Dufferin's career to link the landowning and aristocratic culture he was born into with his experience of governing across the British Empire, in Canada, Egypt, Syria and India. This book argues that there was a defined conception of aristocratic governance and purpose that infused the political and imperial world and which was based on two elements: the inheritance and management of a landed estate and a well-defined sense of 'rule by the best'. It identifies a particular kind of atmosphere of empire and aristocracy, one which was riven with tensions and angst, as those who saw themselves as Britain and Ireland's hereditary leaders were challenged by a rising democracy and in Ireland by a powerful new definition of what Irishness was. It offers a new perspective on both empire and aristocracy in the nineteenth century and will appeal to a broad scholarly audience and the wider public"--
Keywords: Dufferin and Ava, Frederick Temple Blackwood of -- 1826-1902; Dufferin and Ava, Frederick Temple Blackwood / Marquis of / 1826-1902; Diplomats / Great Britain / Biography; Great Britain / Colonies / Administration / History / 19th century; Governors general / Canada / Biography; Colonial administrators / Biography; Viceroys / India / Biography; Imperialism / Social aspects / Colonies / Great Britain / History / 19th century; Ulster (Northern Ireland and Ireland) / Biography; British colonies; Colonial administrators; Colonies / Administration; Diplomats; Governors general; Viceroys; Canada; Great Britain; India; Ireland / Ulster; 1800-1899; Biographies; History; Biografie